T-regulatory cells in transplantology: from preparation to clinical applications - S. N. Sennikov; J. N. Khantakova; N. Y. Knauer (Бюллетень сибирской медицины, 2018)
The intensive study of the cellular approaches for the correction of different pathologies, including immunopathological processes and oncology, as well as the investigation of the immunosuppressive role of the regulatory T-cells (Tregs) made conditions for the development of techniques of the cell-based correction of immune-mediated states, such as autoimmune pathology or transplantation. Since there are few Tregs in periphery and no specific Treg marker is known, the sorting of the whole blood yields insufficient number of cells. That is why it is emerging to search for optimal conditions of Treg generation and expansion using proliferation stimulators and targeted differentiation of the “pure” Treg population that does not involve the proliferation of effector cells. To date, promising results of the Treg immunotherapy to induce allospecific tolerance in recipients having transplanted organs or tissues were obtained in laboratory experiments and clinical trials. The key problems of this therapy are the lack of knowledge about the mechanism of action and the specific phenotype of the most efficient tolerance-inducing Tregs, and the difficulties to obtain stable populations of functional Tregs. Moreover, it is still unknown how to obtain antigen-specific Treg populations and what the mechanism of their action is. In this review the protocols of Treg generation are summarized and the clinical data on the Treg use for the induction of allo-specific tolerance in transplantation are analyzed.